Comparison of plasma lipid peroxidation between migraine and tension type headache in Iraqi patients. - ojs_admin; Suaad Muhammed Abd - Alqader (University of Thi-Qar Journal of Science, 2019)
The oxidant-antioxidant balance disorders underlie a number of acute and chronic diseases of the centralnervous system (CNS). It is believed that oxidative stress plays a role in the pathogenesis of migraine. Thestudy objective is to assess the processes of lipid peroxidation with malondialdehyde (MDA) as its majorindicator. The study was carried out on Iraqi patients to estimate the level of lipid peroxidation in three groupsinclude control group (41subjects), tension-type headache (TTH) (41patients) and migraine (31patients). Themigraine, TTH, and control groups were significantly different on the measures of MDA. The study showedthat the migranieurs were significantly different from other two groups with respect to MDA (p<0.001). Nosignificant difference between males and females within each of the three groups (p >0.05). The onlysignificant difference between females’ age-groups was reported between (15-27years) and (28-40years) yearsold-groups (according to Games-Howell test (P=0.013) while Tukey HSD and Dunnett test contradicted theexits of any differences between them (P>0.05). According to the major similarity between aged-groups forboth males and females in the three groups, it can be concluded that MDA level is not affected by age.